Study on effectivity of black tea as adjuvant therapy in improving neurocognitive performance of patients with early onset of Alzheimer by Montreal Cognitive Assessment - Mitra, Analava (International Journal of Pharmaceutical & Biological Archive, 2017)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder leading to significant deterioration in neurocognitive performance of the patients. The disease puts great financial as well as physical and emotional implications on caregivers cum family. Apart from western classical medicine the disease can also be treated non-pharmacologically viz. adjuvant therapy with Black tea, a very popular beverage in Indian context. This research aims to study the effectivity of black tea as an adjuvant therapy with standard drug Donepezil in improving the cognitive performance of patients with early onset of Alzheimer evaluated by psychometric assessment using Montreal Cognitive Assessment (MoCA) Scale which is a simple, rapid and reliable screening tool to identify cognitive problems. The average MoCA score of normal controls at baseline was 28.4±1.11 and a score of 28.6±0.98 was observed after a follow up of 6 months. Initially, patient volunteers with early onset of Alzheimer who were given the drug Donepezil had an average score of 19.9±1.32 at baseline that was improved to 21.5±1.16 after 6 months. However patient volunteers who were provided with 6 cups of black tea along with the drug Donepezil showed an improvement of score from 19.8±1.31 to 22.1±1.21 after 6 months follow up.